2021
DOI: 10.1038/s41420-021-00683-x
|View full text |Cite
|
Sign up to set email alerts
|

The selective degradation of sirtuins via macroautophagy in the MPP+ model of Parkinson’s disease is promoted by conserved oxidation sites

Abstract: The sirtuin (SIRT) protein family has been of major research interest over the last decades because of their involvement in aging, cancer, and cell death. SIRTs have been implicated in gene and metabolic regulation through their capacity to remove acyl groups from lysine residues in proteins in an NAD+-dependent manner, which may alter individual protein properties as well as the histone–DNA interaction. Since SIRTs regulate a wide range of different signaling cascades, a fine-tuned homeostasis of these protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…Baeken et al . [78] reported that oxidative stress induced SIRTs autophagic degradation in dopaminergic neurons in in vitro PD models. The authors hypothesized that the hyper-acetylation of the proteome upon SIRT depletion could have a protective role against oxidative damage by favoring acetylation-mediated transcriptional activation and preventing lysine cross-linking with other amino acid residues or nucleic acids.…”
Section: Discussionmentioning
confidence: 99%
“…Baeken et al . [78] reported that oxidative stress induced SIRTs autophagic degradation in dopaminergic neurons in in vitro PD models. The authors hypothesized that the hyper-acetylation of the proteome upon SIRT depletion could have a protective role against oxidative damage by favoring acetylation-mediated transcriptional activation and preventing lysine cross-linking with other amino acid residues or nucleic acids.…”
Section: Discussionmentioning
confidence: 99%
“…also reported that NAD + supplementation could be utilized in a broad spectrum of NAD + deficiency‐related pathologies, such as cancer, infection, acute injury, metabolism‐related disorders, and neurodegenerative diseases. [ 50–52 ]…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al also reported that NAD + supplementation could be utilized in a broad spectrum of NAD + deficiency-related pathologies, such as cancer, infection, acute injury, metabolism-related disorders, and neurodegenerative diseases. [50][51][52] Mitochondria, as energy plants, participate in signal transmission, cell differentiation, oxidative stress reactions, and calcium homeostasis. [53] Triphenylphosphonium cation (TPP + ) is the most adopted moiety that can easily and efficiently permeate the mitochondrial inner membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative damage, inflammation and high glucose levels caused senescence in endothelial cells, which was associated with a decrease in SIRT7 levels and as a result an increase in miR-335-5p levels [ 90 ]. In this regard, SIRT7, like other sirtuins, is susceptible to the effects of endogenous ROS, particularly hydrogen peroxide, which cause its carbonylation and subsequent autophagic degradation [ 91 ]. On the other hand, with the number of passages, the cultures of primary mammary epithelial cells increased the expression of SIRT7, as well as the number of cells positive for β-galactosidase and with high levels of expression of p16 INK4a and p21 CIP1 [ 92 ].…”
Section: Sirt7 Association With Agingmentioning
confidence: 99%